Wagner's Law and Peacock and Wiseman's Displacement Effect in European Union Countries: A Panel Data Study - Magazzino, Cosimo; Giolli, Lorenzo; Mele, Marco (International Journal of Economics and Financial Issues, 2015)
Wagner's Law is the first model of public expenditure in the history of public finance. It suggests that during the process of economic development the share of public spending in national income tends to expand (Wagner, 1883). Nevertheless, Peacock and Scott in 2000 wrote a paper entitled “The curious attraction of Wagner's law”, explaining the reasons for why this (apparently) outworn theory is still studied by modern economists. On the other hand, Keynes (1936) considered public spending as an exogenous factor to be used as a policy instrument to influence growth. Moreover, Peacock and Wiseman (1961) presented the displacement effect, according to which during times of war tax rates are increased to generate more revenues, sustaining the increase in defense spending. While Peacock and Wiseman (1979) surveys the literature on public expenditure growth. This paper aims to analyze the relationship between public expenditure and aggregate income in EU countries, for the period 1980-2013, using panel data methodologies. After a brief introduction, a survey of the economic literature on this issue is discussed. Then, panel data tests on stationarity, cross-dependence, cointegration, and causality are shown. Finally, some notes on policy implications conclude the paper. Keywords: Wagner's Law; public expenditure; GDP; EMU; panel data JEL Classifications: C23; E60; H50; H60